IHD para medir simultáneamente en 2D, usando dos fuentes independientes de luz láser con longitud de coherencia grande - Saucedo, T.; Pérez-Arrieta, L.; Hinojosa, S.; Rivera, J.M. (Revista Mexicana de Física, 2013)
One presents an arrangement to measure simultaneously two orthogonal components of deformation in the surface of an object. The arrangement, based in digital holographic interferometry, uses two lasers to record two holograms independently in a single frame from the camera CCD. The arrangement is proved by a metallic plate that changes lightly his dimensions to be heated. Recent works in the development of this type of arrangement, show constraints in the fact to not use light sources with relatively large coherence length. This arrangement is exempt from this limitation.